2023
DOI: 10.3390/ijms24032399
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Gut Microbiome and Trimethylamine Oxide in Atherosclerosis and Age-Related Disease

Abstract: The gut microbiome plays a major role in human health, and gut microbial imbalance or dysbiosis is associated with disease development. Modulation in the gut microbiome can be used to treat or prevent different diseases. Gut dysbiosis increases with aging, and it has been associated with the impairment of gut barrier function leading to the leakage of harmful metabolites such as trimethylamine (TMA). TMA is a gut metabolite resulting from dietary amines that originate from animal-based foods. TMA enters the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 204 publications
0
9
0
Order By: Relevance
“…This increases the risk of cardiometabolic diseases, including obesity, metabolic syndrome, and atherosclerosis ( Nogal et al, 2021 ). Elevated circulating TMAO levels promote systemic inflammation and oxidative stress ( El Hage et al, 2023 ). The positive association between atherosclerosis and AA ( Liu et al, 2016 ) and the additive effects of obesity on asthma risk and severity are noteworthy ( Michalovich et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This increases the risk of cardiometabolic diseases, including obesity, metabolic syndrome, and atherosclerosis ( Nogal et al, 2021 ). Elevated circulating TMAO levels promote systemic inflammation and oxidative stress ( El Hage et al, 2023 ). The positive association between atherosclerosis and AA ( Liu et al, 2016 ) and the additive effects of obesity on asthma risk and severity are noteworthy ( Michalovich et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are originally referred to as the beneficial flora in yogurt; they affect health by stimulating intestinal flora, interfering with the host immune response, reducing cholesterol absorption, etc [ 113 ]. Prebiotics are defined as a particular fermentation component that promotes the growth of probiotics in the human intestinal tract and the function of the body’s immune system; thus, prebiotics are often used as a health food, and lactulose is widely used as a common clinical preparation [ 114 ]. Synbiotics are a combination of probiotics and prebiotics, which have characteristics of both and have a more significant and lasting effect on the adjustment of intestinal microecology [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trimethylamine oxide (TMAO) is a compound produced through intestinal microbial metabolism and is commonly associated with the consumption of fish, red meat, and other foods rich in choline and L-carnitine ( 239 ). Studies have demonstrated that elevated levels of TMAO are linked to the promotion of plaque formation, inflammatory responses, and an increased risk of cardiac events ( 240 , 241 ). TMAO may also exacerbate the occurrence and progression of MI by damaging arterial endothelial function and inducing atherosclerosis.…”
Section: Single-omics Approachesmentioning
confidence: 99%